Genotype of angiotensin converting enzyme for elite female taekwondo players in Egypt - Elsawy, G.; Shaban, A. (Science, Movement & Health, 2014)
Purpose. Despite the worldwide popularity of amateur taekwondo, research focused on the physiological demands of the sport is limited. The physiological profile of elite female taekwondo players is presented. The purpose of the present investigation was to describe the physiological profile of elite female taekwondo players. Methods. With the Local Ethics Committee approval, (11) international standard female TKD fighters provided written informed consent and participatedin this study. All participants were members of Egyptian National Taekwondo Team. All of them have trained TKD for at least (7) years. Three different women weight categories (up to 51, up to 55and up to 59) were included in the study. Results. The present study provides that DD Frequencyis (4 -36%), ID Frequencyis (5- 45%) and II Frequencyis (2- 18%). Adding no statistically significant differences in chi - square test between the three types of angiotensin converting enzymegene for elite female taekwondo players. Conclusions. No correlation coefficient between the three types of angiotensin converting enzymegene and physical characterizes for elite female taekwondo players. This information is also available to the coaches and can contribute to the general strategy employed by taekwondo players and for a specific match.